An intelligent switching control for a mixed separation thickener process. (December 2016) - Chai, Tianyou; Jia, Yao; Li, Haibo; Wang, Hong
Abstract: The mixed separation thickening process (MSTP) of hematite beneficiation is a strong nonlinear cascade process. During its operation, some large random disturbances generated from the flotation middling would cause the underflow slurry flowrate (USF) to fluctuate frequently, leading to the deterioration of the concentrate grade. In this paper, a novel intervals intelligent switching control method is proposed. This controller includes a USF presetting unit via a one-step optimal proportional and integral (PI) control with unmodeled dynamics compensation, a fuzzy reasoning based USF setpoint compensator and a switching mechanism using rule based reasoning. Both a simulated experiment and a real industrial application show that the underflow slurry density (USD), the USF and the variation ratio of the USF can all be controlled within their targeted ranges when the proposed control strategy is used.